Efficacy and Safety of Intracavernosal Alprostadil in Diabetic Patients with Erectile Dysfunction - Doshi, Sanjay Lalitchandra (2001)
Erectile dysfunction is a common complication of Diabetes Mellitus. Intracavernosal Alprostadil, the naturally occurring form of Prostaglandin E 1, has been used successfully in the treatment of erectile dysfunction. Results with Alprostadil have shown a poorer response, shorter duration of action and need for higher dosage in diabetic patients with erectile dysfunction when compared to the general population. No study targeted specifically to the diabetic population has been completed with Alprostadil so far.